Rotation Effects on Coupled Heat and Mass Transfer by Unsteady MHD Free Convection Flow in a Porous Medium Past an Infinite Inclined Plate - Zulkhibri, Ismail; Khan, Ilyas; Nadirah, Mohd Nasir; Rahimah, Jusoh; Mohd Zuki, Salleh; Sharidan, Shafie (2014)
The effects of rotation on coupled heat and mass transfer by unsteady magnetohydrodynamic (MHD) free convection flow in a porous medium past an infinite inclined plate has been investigated. Exact solution using Laplace transforms technique has been obtained for the velocity, temperature and concentration fields. The analytical expressions for nondimensional skin-friction, Nusselt number and Sherwood number have been computed. The solutions of rotation parameters and inclination angle influences the flow fields have been discussed in detail. It is found that inclination angle tend to retard fluid flow in the primary and secondary flow directions, whereas rotation has a retarding influences on the primary flow direction but to accelerate in the secondary flow direction.